Mechanisms of FSH synthesis: what we know, what we don't, and why you should care - Bernard, Daniel J.; Fortin, Jérôme; Wang, Ying; Lamba, Pankaj (Fertility and sterility, 2010)
The pituitary gonadotropin hormones, FSH and LH, are key regulators of reproductive physiology. Though the two hormones are produced by the same cell type, often in response to the same endocrine and paracrine regulators, they sub-serve different biological functions and their synthesis and secretion are differentially regulated. This stems largely from differences in transcriptional, post-transcriptional, and post-translational regulation of their unique β subunits. That is, both hormones are dimeric glycoproteins and share a common α subunit. Their unique β subunits, however, derive from different genes encoding distinct proteins. Past and recent research indicates synthesis and release of the two hormones are subject to extensive and independent regulation. LH appears to be secreted predominantly via the regulated secretory pathway, whereas FSH release is largely constitutive. As such, investigations of FSH-β subunit synthesis may lend direct insight into mechanisms underlying patterns of secreted FSH, more so than investigations of the LHβ subunit. Here, we review recent investigations of transcriptional regulation of the FSH-β subunit gene from different mammalian species, including humans. The results reveal both conserved and species-specific regulatory mechanisms that might contribute to inter-species variation in FSH release.